Hungary : Staff Report for the 2011 Article IV Consultation and Second Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2012)
This 2011 Article IV Consultation highlights that economic growth in Hungary is slowing and market perception of recent policy measures has been negative. The eurozone crisis is weighing on Hungary's external demand. Fiscal and monetary policies are facing constraints, given financial market pressures and inflationary pressures. Executive Directors have noted that the rebound from the crisis has been modest and vulnerabilities remain high. Directors have therefore underscored the need for a well-crafted policy mix that restores confidence in economic governance, anchors the ongoing adjustment, and strengthens economic institutions.